Role of inhibin B in detecting recurrence of granulosa cell tumors of the ovary in postmenopausal patients. Issue 6 (23rd April 2021) - Portuesi, Rosalba; Loppini, Alessandro; Mancari, Rosanna; Filippi, Simonetta; Colombo, Nicoletta
Abstract : Introduction: Several biomarkers have been proposed for the detection of recurrences in adult-type granulosa cell tumors of the ovary. Here we validate the value of inhibin B in detecting recurrences and investigate its role in guiding follow-up examinations and treatment strategies in postmenopausal patients with ovarian adult-type granulosa cell tumors. Methods: Data from 140 patients with a diagnosis of adult-type granulosa cell tumor of the ovary referred to the European Institute of Oncology of Milan from January 1996 to March 2016 were retrospectively collected. Among these, we selected data from 47 postmenopausal women for whom serial inhibin B measurements and related imaging examinations were performed according to the follow-up program, with a total of 315 serum inhibin B samples, together with the corresponding clinical examination, and 180 imaging examinations, confirming the presence or absence of macroscopic disease. Results: At a cut-off of 7 pg/mL, inhibin B levels were significantly correlated with the presence/absence of disease (p<0.01), with a sensitivity of 98.8% (95% confidence interval (CI) 95.8% to 99.9%) and a specificity of 88.9% (95% CI 82.6% to 93.5%). Further, inhibin B was positively correlated with the size of the lesion, and levels were significantly higher in patients with larger lesions also at a cut-off size of 3 cm (total diameter). Logistic regression showed that 15.6 pg/mL, 44.6 pg/mL, and 73.6 pg/mL inhibin B corresponded to 25%, 50%, and 75% probability of having an abnormal computer tomography scan, respectively. Conclusions: Our results confirmed that inhibin B is a sensitive and specific marker for adult-type granulosa cell tumors of the ovary that may be used during follow-up for detection of recurrences. Moreover, it could guide clinicians in the decision regarding when to perform imaging, avoiding redundant interventional tests in the absence of clinical suspicion.